2014
DOI: 10.1111/ijd.12506
|View full text |Cite
|
Sign up to set email alerts
|

Occult tinea pedis in an Israeli population and predisposing factors for the acquisition of the disease

Abstract: The prevalence of occult tinea pedis is similar to that of clinical tinea pedis. This may imply that patients with subclinical infection carry a risk for transmitting disease similar to that of clinical carriers. This is of great importance in the prevention and management of the disease as high-risk asymptomatic carriers can be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
11
2
Order By: Relevance
“…The only commonality between these studies and ours is the frequency of skin mycoses, which, in addition to bacterial infections, was the second leading cause of infectious skin changes in our patients. This is not surprising since mycoses, especially in the form of tinea manuum and tinea pedis, are very common in the general population with a lifetime prevalence of 6.5-14% 37,38 and 15-25%, 39 respectively.…”
Section: Infectious Skin Diseases In Mentally Ill Patientsmentioning
confidence: 99%
“…The only commonality between these studies and ours is the frequency of skin mycoses, which, in addition to bacterial infections, was the second leading cause of infectious skin changes in our patients. This is not surprising since mycoses, especially in the form of tinea manuum and tinea pedis, are very common in the general population with a lifetime prevalence of 6.5-14% 37,38 and 15-25%, 39 respectively.…”
Section: Infectious Skin Diseases In Mentally Ill Patientsmentioning
confidence: 99%
“…Clinical signs of onychomycosis include thickened, discolored and crumbling nails that may be partially detached from the nail bed . The manifestation of clinical signs is the determining factor that prompts the clinician to perform mycological testing; however, infectious organisms may be present on the skin and in toenails despite the absence of clinical signs of foot or nail infection …”
mentioning
confidence: 99%
“…3 The manifestation of clinical signs is the determining factor that prompts the clinician to perform mycological testing; 4 however, infectious organisms may be present on the skin and in toenails despite the absence of clinical signs of foot or nail infection. 5 Previous studies have investigated the presence of fungal organisms in the normal-appearing toenails of patients with dermatophytosis. Davies reported that 9Á0% of 3955 normal, healthy-looking nail samples from patients infected with T. rubrum were either KOH-and/or culture-positive for the fungus.…”
mentioning
confidence: 99%
“…Indeed, the average humidity of the fourth interdigital area in the summer was 80%, average maximum humidity was 84%, maximum humidity was 91% and average dew point was 31°C. A humid environment is important for the development of tinea infections; 25,26,28,30,31,33 however, high humidity was not the major factor contributing to the development of tinea manuum, tinea corporis and tinea capitis, 31 but rather the high-temperature and high-humidity environment. Based on these studies, the following three factors can be considered necessary for tinea development: an environment with high temperature and high humidity (temperature and humidity), sufficient dermatophyte adhesion time (time) and fine scratches on the skin or nails (injury).…”
Section: Conditions Required For Dermatophyte Infectionmentioning
confidence: 99%
“…Based on these studies, the following three factors can be considered necessary for tinea development: an environment with high temperature and high humidity (temperature and humidity), sufficient dermatophyte adhesion time (time) and fine scratches on the skin or nails (injury). 4,[32][33][34][35][36] Reducing these three conditions can prevent exacerbating TP infections. In addition, the length of time that footwear is worn is also thought to be a risk factor for TP.…”
Section: Conditions Required For Dermatophyte Infectionmentioning
confidence: 99%